MANAJEMEN DISIPLIN SISWA - Endang Partiyem (Manajer Pendididikan, 2015)
The purpose of this study was to describe: 1) planning discipline in primary school students 58 Lubuklinggau, 2) organizing student discipline in primary school 58 Lubuklinggau, 3)the application or implementation of student discipline at the Elementary School 58 Lubuklinggau, 4) supervision of student discipline at the Elementary School 58 Lubuklinggau, and 5) monitoring and evaluation of student discipline at the Elementary School 58 Lubuklinggau. In this research approach used is deskriftive qualitative, because the data collected and the analysis is more qualitative. The conclusions of this study is the management discipline in SD Negeri 58 lubuklinggau have attempted to apply managerial discipline well.Keywords: management, discipline, student